THU0185 Biologics-Induced Autoimmune Renal Abnormalities: Systematic Literature Review and Analysis of A Monocentric Cohort of 707 Adult Patients Affected by Rheumatic Disease. (10th June 2014) - Piga, M.; Chessa, E.; Ibba, V.; Mura, V.; Vacca, A.; Garau, P.; Gabba, A.; Porru, G.; Cauli, A.; Mathieu, A.
Abstract : Background: The use of biological drugs has been linked with the paradoxical development of systemic and organ specific autoimmune processes. Objectives: To describe the features of biologics-induced autoimmune renal abnormalities (AIRA) through a systematic review and the analysis of 707 adult patients with inflammatory rheumatic disease (IRD) followed-up in a third level center of Rheumatology. Methods: Using PubMed a systematic review was carried out according to PRISMA guidelines and included the following Mesh terms: "Arthritis, Rheumatoid" OR "Arthritis, Psoriatic" OR "Spondylitis, Ankylosing" AND "infliximab" OR "TNFR-Fc fusion protein" OR "golimumab" OR "adalimumab" OR "certolizumab pegol" OR "rituximab" OR "tocilizumab" OR "abatacept" AND "Glomerulonephritis" OR "Nephrotic Syndrome" OR "Nephrosis, Lipoid". Last Medline was performed on the 31/08/2013. A retrospective analysis of 707 adult patients with IRD, of which 427 Rheumatoid Arthritis (RA), 168 Ankylosing Spondylitis (AS) and 112 Psoriatic Arthritis (PsA), treated with biologics between 2004 and 2013, was performed. All patients have been prospectively followed-up and have had blood tests and urine analysis at least three times per year. The aim was to identify those patients that developed biologics-induced AIRA. According to clinical manifestations and kidney histology the cases identified by systematic review and cohort analysis were classified as: A) Glomerulonephritis associated with systemic vasculitis (GNSV), B) glomerulonephritis in lupus-like syndrome (GNLS), C) other autoimmune renal disorders (OARD). Results: The literature search identified 1687 articles from which 22 were considered relevant for the present study for a total of 28 case reports. The retrospective cohort analysis retrieved 3 cases. Data have been pooled. Twenty-three patients identified were on biologics treatment because RA, 4 had AS and 4 had PsA. TNF-alpha blockers were responsible for AIRA in all identified cases: 17 etanercept, 9 adalimumab and 7 infliximab. AIRA usually appeared within 12 months since the beginning of anti-TNF-alpha therapy, but 8 cases were diagnosed later. The 31 cases identified were classified as: 12 with OARD (5 membranous GN, 3 IgA nephropathy, 1 mesangial GN, 1 minimal change GN, 1 necrotizing GN, 1 not biopsied), 11 with GNSV (3 necrotizing-crescentic GN, 2 necrotizing GN, 2 pauci-immune GN, 1 Schönlein-Henoch IgA nephropathy, 3 not biopsied), 8 with GNLS (1 class III, 3 class IV, 4 not biopsied). Age at onset was younger in GNLS (38.9±13.6 years, 7 female) than in OARD (54.7±13.0 years; 6F) and GNSV (48.6±14.5 years, 6F). Better prognosis was associated with GNLS (75% complete and 25% partial resolution) and treatment with corticosteroids and immunosuppressant, whilst worse prognosis was associated with GNSV, OARD and lack of anti-TNF-alpha withdrawal. End stage renal failure was reported in 2 cases with GNSV and 1 with OARD whilst 1 dead was reported in GNSV. Conclusions: Patients with IRD may suffered from biologics-induced AIRA which are apparently associated only with anti-TNF-alpha and although rare they may be life-threatening. If AIRA occur biologics must be discontinued and the patient should be treated according to clinical manifestations and biopsy findings. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4524